Chemical Vapor Deposition of 3C-SiC on [100] Oriented Silicon at low Temperature < 1200°C for Photonic Applications - Kollmuß, Manuel; Köhler, Johannes; Ou, H.; Fan, W.; Chaussende, D.; Hock, Rainer; Wellmann, Peter (Materials Science Forum, 2022)
3C-SiC films have been grown on [100] n-doped Si substrates in a horizontal cold wall CVD reactor. Without the use of plasma enhancement, the precursors silane and propane are used to deposit silicon carbide films at T < 1200°C. The structure of the grown films has been investigated via FESEM, XRD and Raman spectroscopy. It has been found that the growth rates are between 200 and 300 nm/h. Additionally, structural analysis give evidence of polycrystalline phases. Reasons for that could be insufficient cracking of the precursors and homogenous nucleation of Si species in the gas phase.
CRIS-Team Scopus Importer:2022-12-16
Keywords: 3C-SiC; cold wall reactor; CVD; heteroepitaxy; low temperature; void

Effect of Growth Conditions on the Surface Morphology and Defect Density of CS-PVT-Grown 3C-SiC - Kollmuß, Manuel; La Via, Francesco; Wellmann, Peter (Crystal Research and Technology, 2023)
A systematic approach to determine the most crucial growth parameters and their effect on the surface morphology and defect density of sublimation grown (001) cubic silicon carbide (3C-SiC) is conducted. Close space physical vapor transport (CS-PVT) growth on 3C-SiC and 4° off oriented homoepitaxial chemical vapor deposition (CVD) grown seeding layers is performed. For each growth run, one growth parameter, e.g., temperature, pressure, or N2 flux is varied, while the other parameters are kept constant. Raman spectroscopy, potassium hydroxide (KOH) etching, as well as optical microscopy and atomic force microscopy (AFM) are used for the sample characterization. Step-flow-controlled growth is observed on all grown samples, while the stacking fault density is generally reduced with respect to the seeding layers. Increased temperature as well as increased pressure leads to roughening of the growth surface attributed to step bunching, while their effect on the stacking fault density seems to be only minor in the analyzed parameter range. Areas of strongly enhanced step bunching are present on all samples, and this effect is more pronounced at higher temperature and pressure. Increased nitrogen doping leads to a decreased stacking fault density but also increases the length of remaining stacking faults. The surface morphology is influenced by N2 on a macroscopic level rather than on microscopic scale.
CRIS-Team Scopus Importer:2023-05-26
Keywords: 3C-SiC; defect density; nitrogen doping; sublimation growth; surface morphology

In situ bow reduction during sublimation growth of cubic silicon carbide - Kollmuß, Manuel; Mauceri, Marco; Roder, Melissa; La Via, Francesco; Wellmann, Peter (Reviews on Advanced Materials Science, 2022)
Sublimation growth of cubic silicon carbide (3C-SiC) with diameters of 50 and 100 mm was performed on freestanding homoepitaxial grown seeds. For both seeds and sublimation grown crystals, two different relaxation axes with varying curvature could be observed with the higher bent axis aligned perpendicular to the original wafer flat. A general reduction in the wafer bow independent of the starting curvature and size of the seeds could be observed. Using the X-ray imaging, we could observe in situ that the bow reduction is linked to the growth of new material and cannot be initiated by heat up or cool down processes alone. Raman spectroscopy of the grown crystals revealed that the observed flattening goes along with a tensing of the seeding layers while the surface of the crystals remains free of a stress gradient. A slight concave bending of lattice planes along the main relaxation axis could be observed by high-resolution XRD rocking curve measurements while for the lower bent axis, no lattice plane bending occurred. Full width half maximum values of the (002) reflection showed values as low as 67 arcseconds proofing the possibility to grow large-area, high-quality 3C-SiC using sublimation growth.
CRIS-Team WoS Importer:2023-01-27

Investigation of amorphous-SiC thin film deposition by RF magnetron sputtering for optical applications - Chaussende, Didier; Tabouret, Vincent; Crisci, Alexandre; Morais, Magali; Coindeau, Stéphane; Berthomé, Gregory; Kollmuß, Manuel; Wellmann, Peter; Jomard, François; Pinault-Thaury, Marie Amandine; Lu, Yaoqin; Shi, Xiaodong; et al. (Materials Science in Semiconductor Processing, 2024)
Silicon carbide (SiC) is a rapidly emerging material for photonic applications, thanks to its exceptional optical properties. To be used as a waveguide, SiC thin films must be deposited directly on silica at low temperature. Amorphous SiC films were deposited by RF magnetron sputtering using a single source of high-purity polycrystalline SiC. A systematic study of the chemical, structural and optical properties of the films was carried out, using a combination of XRD, XPS, SIMS, spectroscopic ellipsometry, Raman spectroscopy and UV–Vis absorption spectroscopy. The aim was to link deposition conditions to film properties. By exploring a three-parameter space (RF power, substrate temperature, pressure), we have demonstrated that RF power is the main parameter which controls the entire deposition process and film properties. By simply adjusting the RF plasma power between 150 and 450 W, it is possible to adjust the refractive index at a wavelength of 1.5 μm in the range 2.50–2.75 and vary the bandgap from 2.5 to 1.7 eV. This is attributed to a slight variation in film composition, particularly in terms of Si/C ratio and C–C bond concentration.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Amorphous; Deposition process; Magnetron sputtering; Optical properties; Silicon carbide

Large Area Growth of Cubic Silicon Carbide Using Close Space PVT by Application of Homoepitaxial Seeding - Kollmuß, Manuel; Schöler, Michael; Anzalone, R.; Mauceri, M.; La Via, F.; Wellmann, Peter (Materials Science Forum, 2022)
One setback that hinders the breakthrough of cubic silicon carbide is the lack of suitable seeding material for sublimation growth methods such as PVT. We present the growth of large area cubic silicon carbide material, up to a diameter of 100 mm, with a sublimation growth process called close spaced PVT (CS-PVT). Freestanding 3C-SiC seeding layers were grown by a homoepitaxial CVD process. Subsequently CS-PVT was used to grow crystals up to a thickness of 1 mm. To prevent backside sublimation a carbon containing layer was applied as protection. Due to the presence of a wafer bow as well as a rough backside of the used seeds additional effort was necessary to apply the coating. After growth no visible curvature was present independent of the grown layer thickness and sample size. Raman spectroscopy was performed on the seeds and grown crystals, showing that the overall stress level of the material was reduced by CS-PVT.
Created from Fastlane, Scopus look-up
Keywords: 3C-SiC; bow reduction; large-area growth; stress reduction; Sublimation growth

Multiscale Simulations for Defect-Controlled Processing of Group IV Materials - Calogero, Gaetano; Deretzis, Ioannis; Fisicaro, Giuseppe; Kollmuß, Manuel; La Via, Francesco; Lombardo, Salvatore F.; Schöler, Michael; Wellmann, Peter; La Magna, Antonino (Crystals, 2022)
Multiscale approaches for the simulation of materials processing are becoming essential to the industrialization of future nanotechnologies, as they allow for a reduction in production costs and an enhancement of devices and applications. Their integration as modules of "digital twins", i.e., a combined sequence of predictive chemical-physical simulations and trained black-box techniques, should ideally complement the real sequence of processes throughout all development and production stages, starting from the growth of materials, their functional manipulation and finally their integration in nano-devices. To achieve this framework, computational implementations at different space and time scales are necessary, ranging from the atomistic to the macro-scale. In this paper, we propose a general paradigm for the industrially driven computational modeling of materials by deploying a multiscale methodology based on physical-chemical simulations bridging macro, meso and atomic scale. We demonstrate its general applicability by studying two completely different processing examples, i.e., the growth of group IV crystals through physical vapor deposition and their thermal treatment through pulsed laser annealing. We indicate the suitable formalisms, as well as the advantages and critical issues associated with each scale, and show how numerical methods for the solution of the models could be coupled to achieve a complete and effective virtualization of the process. By connecting the process parameters to atomic scale modifications such as lattice defects or faceting, we highlight how a digital twin module can gain intrinsic predictivity far from the pre-assessed training conditions of black-box "Virtual Metrology" techniques.
CRIS-Team WoS Importer:2023-01-20

New approaches and understandings in the growth of cubic silicon carbide - Via, Francesco La; Zimbone, Massimo; Bongiorno, Corrado; La Magna, Antonino; Fisicaro, Giuseppe; Deretzis, Ioannis; Scuderi, Viviana; Calabretta, Cristiano; Giannazzo, Filippo; Zielinski, Marcin; Anzalone, Ruggero; Mauceri, Marco; et al. (Materials, 2021)
In this review paper, several new approaches about the 3C‐SiC growth are been presented. In fact, despite the long research activity on 3C‐SiC, no devices with good electrical characteristics have been obtained due to the high defect density and high level of stress. To overcome these problems, two different approaches have been used in the last years. From one side, several compliance substrates have been used to try to reduce both the defects and stress, while from another side, the first bulk growth has been performed to try to improve the quality of this material with respect to the heteroepitaxial one. From all these studies, a new understanding of the material defects has been obtained, as well as regarding all the interactions between defects and several growth parameters. This new knowledge will be the basis to solve the main issue of the 3C‐SiC growth and reach the goal to obtain a material with low defects and low stress that would allow for realizing devices with extremely interesting characteristics.
CRIS-Team Scopus Importer:2021-10-01
Keywords: 3C‐SiC; Bulk growth; Compliant substrates; Defects; Heteroepitaxy; Stress

Novel Photonic Applications of Silicon Carbide - Ou, Haiyan; Shi, Xiaodong; Lu, Yaoqin; Kollmuß, Manuel; Steiner, Johannes; Tabouret, Vincent; Syväjärvi, Mikael; Wellmann, Peter; Chaussende, Didier (Materials, 2023)
Silicon carbide (SiC) is emerging rapidly in novel photonic applications thanks to its unique photonic properties facilitated by the advances of nanotechnologies such as nanofabrication and nanofilm transfer. This review paper will start with the introduction of exceptional optical properties of silicon carbide. Then, a key structure, i.e., silicon carbide on insulator stack (SiCOI), is discussed which lays solid fundament for tight light confinement and strong light-SiC interaction in high quality factor and low volume optical cavities. As examples, microring resonator, microdisk and photonic crystal cavities are summarized in terms of quality (Q) factor, volume and polytypes. A main challenge for SiC photonic application is complementary metal-oxide-semiconductor (CMOS) compatibility and low-loss material growth. The state-of-the-art SiC with different polytypes and growth methods are reviewed and a roadmap for the loss reduction is predicted for photonic applications. Combining the fact that SiC possesses many different color centers with the SiCOI platform, SiC is also deemed to be a very competitive platform for future quantum photonic integrated circuit applications. Its perspectives and potential impacts are included at the end of this review paper.
CRIS-Team Scopus Importer:2023-02-24
Keywords: integrated photonics; material growth; silicon carbide

Prospects of bulk growth of 3C-SiC using sublimation growth - Wellmann, Peter; Schuh, Philipp; Kollmuß, Manuel; Schöler, Michael; Steiner, Johannes; Zielinski, M.; Mauceri, M.; La Via, F. (Materials Science Forum, 2020)
Free standing 3C-SiC wafers with a dimeter of 50 mm and a thickness of ca. 0.8 mm have been grown on a regular base using 3C-SiC CVD seed transfer from Si wafers to a poly-SiC-carrier and a sublimation epitaxy configuration. Up to the thickness of almost 1 mm, stable growth conditions of the cubic polytype have been achieved. The high supersaturation was kept stable by the proper design of the hot zone that enables a high axial temperature gradient at the growth interface. The Si-rich gas phase was realized by the application of a Tantalum getter that was integrated into the graphite-based growth cell. Furthermore, an adaption of the growth setup allowed the growth of 3C material with a diameter of 95 mm and bulk material up to 3 mm on 25 mm diameter. Computer simulations were used to determine the supersaturation of the growth setup for different source-to-seed distances. The minimum supersaturation necessary for stable growth of cubic SiC was found to be higher 0.1 for seeds already containing the required 3C polytype.
CRIS-Team Scopus Importer:2020-09-04
Keywords: 3C-SiC; Bulk; Large-area; Sublimation epitaxy; Supersaturation

Review of Sublimation Growth of SiC Bulk Crystals - Wellmann, Peter; Arzig, Matthias; Ihle, Jonas; Kollmuß, Manuel; Steiner, Johannes; Mauceri, M.; Crippa, D.; Lavia, F.; Salamon,; Uhlmann, N.; Roder, M.; Danilewsky, A.; et al. (Materials Science Forum, 2022)
The review on bulk growth of SiC includes a basic overview on the widely used physical vapor transport method for processing of 4H-SiC boules as well as the discussion of three current research topics: (a) Sublimation bulk growth of large area, freestanding cubic SiC, (b) in-situ Visualization of the PVT Process using 2D and 3D X-ray based imaging and (c) prediction of dislocation formation and motion in SiC using a continuum model of dislocation dynamics (CDD).
Created from Fastlane, Scopus look-up
Keywords: 3C-SiC; 4H-SiC; bulk growth; dislocations; X-ray in-situ visualization

Transfer of Heteroepitaxial Grown 3C-SiC Layers for Application in Optical Frequency Combs - Kollmuß, Manuel; Shi, X.; Ou, H.; Wellmann, Peter (Trans Tech Publications Ltd, 2023)
We developed a process for the fabrication of SiCOI stacks which are a suitable platform for optical devices. Starting from 3C-on-Si samples the silicon substrate was removed by wet chemical etching and the remaining 3C-SiC layers were bonded to two different low refractive substrates (Al2O3 and polycrystalline SiC with a 3 µm thick SiO2 layer on top deposited by PECVD). We found that also bonding onto Al2O3 was possible, the stability of the resulting stack wasn´t strong enough for further processing. In contrast mechanical stable SiCOI stacks could be realized using the oxide coated polycrystalline SiC as substrate. Besides the substrate materials three different bonding approaches (hydrophilic, hydrophobic and adhesive bonding using an HSQ resist) as well as multiple process parameters were analyzed with regard to the bonding performance. The best results could be achieved using the adhesive bonding approach with a bonding temperature ≥ 400°C, a process time ≥ 4 h and a bonding pressure of 96 N/cm2.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Bonding; Cubic SiC; Frequency combs; Thin film transfer